Perbedaan Peningkatan Prestasi Belajar IPA Melalui Pembelajaran Berbasis Masalah dan Inkuiri Terbimbing Pokok Bahasan Energi dan Daya Listrik Kelas IX di SMPN 20 Bandar Lampung - Tsamaniariaty Hidayah; Sulton Djasmi; Undang Rosidin (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
DIFFERENCES IN INCREASED ACHIEVEMENT OF SCIENCE LEARNING THROUGH PROBLEM BASED AND INQUIRY LEARNING GUIDED PRINCIPLES OF ENERGY AND POWER AT GRADE IX OF SMPN 20 BANDAR LAMPUNG. Difference Improving Learning Achievement of Science Through Learning Based On Problem And Discussion Guided Inquiry Energy And Power Supply Of Ninth Grade At Smpn 20 Bandar Lampung. The research aims to know : (1) difference in improving pre-test and post-test of cognitive in learning based of problem. (2) difference in improving pre-test and post-test of cognitive in learning guided inquiry. (3) difference in improving student's post-test of cognitive in learning based of problem and guided inquiry. This research is an experimental research by "pre-tes post-test one group design". Population in this research is all of the students of ninth grade at SMPN 20 Bandar Lampung. Sampling by purposive technique of ninth grade A and ninth grade C. Data is analyzed by mean difference test. Conclusion in this research are: (1) there is a difference in improving between cognitive test score is learning based on problem 18,98. (2) there is a difference in improving cognitive test score in learning guided inquiry 10,85. (3) there is a difference in improving cognitive test score is learning based on problem with cognitive test score in guided learning 3,60.